Persepsi Mahasiswa Akuntansi Mengenai Tax Evasion - Nisrina, Ulfah Laila (Fakultas Ekonomi dan Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2025)
This study examines accounting students’ perceptions of tax evasion using a qualitative descriptive approach through in-depth interviews with students who have taken or are taking taxation courses. The findings indicate that accounting students generally perceive tax evasion as an illegal act that violates professional ethics and social responsibility and harms the state by reducing tax revenue and creating fiscal injustice. However, some students show neutral or ambiguous attitudes toward tax evasion, particularly when influenced by perceptions of tax system unfairness and low trust in government. The study concludes that students’ perceptions of tax evasion are shaped not only by technical taxation knowledge but also by ethical values, educational experiences, and social context, highlighting the importance of strengthening ethics and integrity education in accounting and taxation learning.